Modulation of Apoptotic and Akt/PI3K/mTOR pathways to target Glioblastoma Cells using synthetic compound PGEA-AN - Shafea Saad; Farina Hanif; Shabana Usman Simjee; Shaheen Faizi; Lubna Khan; Ambreen Ashfaque (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the anticancer potential of a novel synthetic derivative of a naturally occurring diterpenoid against glioblastoma. Method: The in vitro study was conducted at the Ojha Campus of Dow University of Health Sciences, Karachi, from February to December 2021, and comprised U87 cells. The 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used to determine the growth inhibitory effect of 16(R and S) – phenylamino-cleroda3, 13(14) Zdiene- 15, 16 olide and standard drug temozolomide against glioblastoma cells, and half-maximal inhibitory concentration was calculated. Microscopy and immunocytochemistry were used to investigate apoptotic morphology and active caspase-3 and B-cell lymphoma 2 (Bcl-2) expression. Quantitative real time polymerase chain reaction was used to investigate the expression of proliferation markers. Data was analysed using SPSS 21. Results: Both the synthetic derivative and the standard drug significantly inhibited growth of U87 cells (p<0.001) with half-maximal inhibitory concentration of 19uM and 185uM, respectively. Apoptotic morphology and upregulation of active caspase-3 protein expression was observed in cells treated with half-maximal inhibitory concentration doses of both the synthetic derivative (p<0.05) and the standard drug (p<0.001), and Bcl-2 was downregulated in both the synthetic derivative (p<0.01) and the standard drug (p=0.05). However, no significant difference was observed in the expression of proliferation markers (p>0.05). Conclusion: The synthetic diterpene derivative PGEA-AN showed growth inhibitory actiity against glioblastoma. Key Words: Temozolomide, Caspase, Glioblastoma, Diterpenes.